481 The curious case of new onset paediatric diabetes and COVID-19. (17th August 2022) - Ponmani, Caroline; Lyttle, Mark; Roland, Damian; Nijman, Ruud; Barrett, Michael; Hulse, Tony; Whittle, Victoria
Abstract : Aims: Paediatric emergency departments saw an unusual increased incidence and severity of disease presentation in children with new onset diabetes in the early phase of the COVID-19 pandemic. The DIMPLES study(Diabetes Mellitus in children and young people presenting to the Emergency Department during the SARS-CoV-2 pandemic) aimed to characterise the features of children presenting to Paediatric Emergency Department with new onset diabetes in the COVID-19 pandemic, exploring the incidence and severity of diabetic ketoacidosis (DKA). Methods: The DIMPLES study is a retrospective multicentre study done across 49 paediatric emergency departments providing a unique perspective of new onset diabetes paediatric diabetes from the frontline. We compared the characteristics of children aged 6 months to 16 years presenting to the Paediatric Emergency Departments across UK and Ireland with new onset diabetes in the pandemic (March 1, 2020 to February 28, 2021) with the children presenting in the same time period over the pre pandemic period (March 1, 2019 to February 28, 2020). Results: During the COVID pandemic year, there were increase from the pre-pandemic year in children with new onset diabetes presenting with DKA (pH <7.3; from 395 to 566; 43% rise), severe DKA (pH <7.1; from 141 to 252; a 79% rise), and admissions to intensive care (from 38 to 72; 89% rise), suggesting an increase in incidence and severity of new-onset diabetes. An increase in the incidence of new onset diabetes from 1015 to 1176 was noted in the pandemic(16% increase compared to an estimated increase of 2-4% per year).The median age of children who presented with new onset diabetes in the pandemic, the duration of symptoms before presentation and the ethnicity was similar to the pre pandemic period. Delay did not appear to be a significant factor in the pandemic compared to the pre pandemic period in the majority of cases. There was a paucity in testing for COVID-19 antibodies, 37/1176 children with new onset diabetes were tested with n=8 children testing positive for IgG/IgM COVID-19 antibodies. 12 children with new onset diabetes tested positive for SARS-CoV-2 on nasopharyngeal swabs, 7 presented with moderate to severe DKA and 3 presented with mild DKA. Conclusion: The DIMPLES study showed an increase in the number and severity of children presenting to the Paediatric Emergency Department with new onset diabetes and DKA in the COVID -19 pandemic. Proving association or causation was challenging given the small number of children tested for COVID-19 antibodies. When the incidence and severity at presentation is interpreted in the context of high levels of SARS-CoV-2 in the community and a low incidence of other viral infectious triggers it appears that COVID -19 may have a role as an accelerator or possibly even a precipitator of new onset diabetes in a genetically predisposed child.